2013
DOI: 10.7860/jcdr/2013/4817.2797
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Intestinal Parasitic Infestation and the Related Profile of the CD4+ Counts in HIV/AIDS People with Diarrhoea in Jaipur City

Abstract: Introduction: Gastrointestinal Tract (GIT) infections are among the most frequent infections in HIV/AIDS patients. The intestinal opportunistic parasitic infections in HIV-infected subjects present most commonly as diarrhoea. A study was conducted to determine the prevalence of enteric parasitic infections in HIV infected patients with diarrhoea, with different levels of immunity. Methods:This study was carried out at the HIV Lab of the Microbiology Department of a tertiary care teaching hospital in Jaipur, Ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 15 publications
2
4
0
Order By: Relevance
“…Oral-anal and oral genital contact predisposes homosexuals to infection with enteric pathogens. 35 IPI was higher among PLHA having CD 4 -T cell counts <200/µl than having ≥200/µl, which shows agreements with reports from other countries regarding IPI in different CD 4 ranges 25,28,36,37 as well as from Nepal. 4,38 In studies conducted in Nepal, more than three-fifth to four-fifth of the HIV patients with CD 4 T-cell count <200 were found having parasitic infections.…”
Section: Discussionsupporting
confidence: 79%
“…Oral-anal and oral genital contact predisposes homosexuals to infection with enteric pathogens. 35 IPI was higher among PLHA having CD 4 -T cell counts <200/µl than having ≥200/µl, which shows agreements with reports from other countries regarding IPI in different CD 4 ranges 25,28,36,37 as well as from Nepal. 4,38 In studies conducted in Nepal, more than three-fifth to four-fifth of the HIV patients with CD 4 T-cell count <200 were found having parasitic infections.…”
Section: Discussionsupporting
confidence: 79%
“…In other studies, the only parasite significantly found more in HIV-positive individuals compared to HIV-negative subjects was Cryptosporidium, which is consistent with the present study (17,18). In Vyas et al study, the prevalence of Cryptosporidium (37.93%) in northern India and the prevalence of Isospora belli (31.3%) in southern India was more than other species (19). Also, in Akinbo et al study in Nigeria in 2010, Cryptosporidium (22.2%) and Isospora belli (7.8%) species were seen as opportunistic infections (6), which are consistent with the present study and some other studies (20)(21)(22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal parasitic coinfection with tuberculosis without HIV infection has been studied in the past [32]. Studies also have shown that coccidian parasites infect the immunocompromised patients suffering from HIV [33,34]. The presence of coccidian parasites in two patients not suffering from HIV, stresses on the need for further investigation into their relevance in non-HIV patients.…”
Section: Discussionmentioning
confidence: 99%